CuO nanoparticles modify bioaccumulation of perfluorooctanoic acid in radish (Raphanus sativus L.). Issue 1 (31st December 2022) - Xu, Yang; Du, Wenchao; Yin, Ying; Sun, Yuanyuan; Ji, Rong; He, Huan; Yang, Shaogui; Li, Shiyin; Wu, Jichun; Guo, Hongyan
ABSTRACT: Research on combined phytotoxicity of perfluorooctanoic acid (PFOA) and nanoparticles is very important for the remediation of PFOA contaminated soil and further assessment for the potential of nano-enhanced phytoremediation. Here, joint effects of PFOA and CuO nanoparticles (nCuO) in plants were studied by exposing radish ( Raphanus sativus L.) to PFOA (4 mg/kg) and nCuO (200 and 400 mg/kg) for 30 days, and measuring for contaminant accumulation, radish biomass, photosynthesis profiles and nutrient contents. Results showed that PFOA accumulated highly in radish organs but showed limited effects on radish biomass. nCuO could increase the transfer rate of PFOA from root to shoot and reduce PFOA accumulation in edible root part, but higher nCuO lead to decreased radish biomass. Reversely, PFOA alleviated the adverse effects of nCuO on leaf photosynthesis and root metabolism of vitamins and amino acids. These results provided basics for exploring possibility of nano-enhanced phytoremediation for PFOA soil pollution.